Malaria and helminth co-infections in school and preschool children: a cross-sectional study in Magu district, north-western Tanzania. - Safari M Kinung'hi; Pascal Magnussen; Godfrey M Kaatano; Coleman Kishamawe; Birgitte J Vennervald (PLoS ONE, 2014)
BACKGROUND: Malaria, schistosomiasis and soil transmitted helminth infections (STH) are important parasitic infections in Sub-Saharan Africa where a significant proportion of people are exposed to co-infections of more than one parasite. In Tanzania, these infections are a major public health problem particularly in school and pre-school children. The current study investigated malaria and helminth co-infections and anaemia in school and pre-school children in Magu district, Tanzania. METHODOLOGY: School and pre-school children were enrolled in a cross-sectional study. Stool samples were examined for Schistosoma mansoni and STH infections using Kato Katz technique. Urine samples were examined for Schistosoma haematobium using the urine filtration method. Blood samples were examined for malaria parasites and haemoglobin concentrations using the Giemsa stain and Haemoque methods, respectively. PRINCIPAL FINDINGS: Out of 1,546 children examined, 1,079 (69.8%) were infected with one or more parasites. Malaria-helminth co-infections were observed in 276 children (60% of all children with P. falciparum infection). Malaria parasites were significantly more prevalent in hookworm infected children than in hookworm free children (p = 0.046). However, this association was non-significant on multivariate logistic regression analysis (OR = 1.320, p = 0.064). Malaria parasite density decreased with increasing infection intensity of S. mansoni and with increasing number of co-infecting helminth species. Anaemia prevalence was 34.4% and was significantly associated with malaria infection, S. haematobium infection and with multiple parasite infections. Whereas S. mansoni infection was a significant predictor of malaria parasite density, P. falciparum and S. haematobium infections were significant predictors of anaemia. CONCLUSIONS/SIGNIFICANCE: These findings suggest that multiple parasite infections are common in school and pre-school children in Magu district. Concurrent P. falciparum, S. mansoni and S. haematobium infections increase the risk of lower Hb levels and anaemia, which in turn calls for integrated disease control interventions. The associations between malaria and helminth infections detected in this study need further investigation.